Herpetofaunal diversity of a natural protected area in the espinal region of central-eastern Argentina - Martinez, Matias Emanuel (2025)
Amphibians are the most endangered vertebrates worldwide (41 % of the species at risk), while reptiles have 21 % of their species at risk. Both taxonomic groups are indicators of ecosystem health. We study the herpetofauna of the Juan Bautista Alberdi Multiple Use Reserve (JBAR), Entre Ríos, Argentina, a natural protected area of the Espinal Ecoregion. Our aims were: analyze the taxonomic composition of the herpetofaunal communities; estimate the species occurrence index, and evaluate and compare Hill´s diversities (0D, 1D y 2D) of the communities among different habitats in the JBAR. We used six different sampling methods and we registered 18 herpetofaunal species. Eleven amphibian species were detected, distributed in five genera and three families. The Hylidae family had the highest species richness (five species representing 45.4 %), followed by Leptodactylidae (36.4 %) and Bufonidae (18.2 %). Seven reptile taxa were detected, belonging to seven different families, each representing 14.3 % of the total. According to the occurrence constancy index, almost all species were rare, making up 94.4 % of the community (n = 17; <25 %), while common species accounted for the remaining 5.6 % (n = 1; > 25 %). Species occurrence was significantly higher in the Tajamar (TA) compared to other habitats (NF: Native Forest, EF: Exotic forest and GR: Grassland). Tajamar also exhibited the highest values in all Hill diversity measures, and the other habitats did not show significant differences between each other in any of the studied parameters. Sample coverage was 84.9 % in TA, 84.6 % in GR, 71.8 % in EF, while NF was 54.2 %. Understanding the current situation of herpetofauna is key to diagnosing and finding solutions to both current and future problems. We hope that our contributions highlight the value of the JBAR´s natural heritage, as a relic of the Espinal Ecoregion.